Study on the Performance of Filters Under Biogas Slurry Drip Irrigation Systems - Shuaijie Wang; Haitao Wang; Xuefeng Qiu; Jiandong Wang; Shuji Wang; Hang Wang; Tao Shen (Agriculture)
Filters are essential components for maintaining the stability of drip irrigation systems, effectively reducing the risk of clogging. However, when applied to slurry drip irrigation systems, the complexity of slurry water quality makes it unclear how different filter types and their combinations affect the hydraulic performance of the system. This study provides a comprehensive performance evaluation of two common filter types and their combinations, considering various flow rates and biogas slurry-to-water ratios under drip irrigation conditions. The results revealed the following key findings: (1) In the application of biogas slurry drip irrigation, an increase in the concentration or flow rate of the slurry significantly affects the hydraulic performance of the filter, increasing the risk of clogging and shortening the operational lifespan. Notably, the impact of changes in slurry concentration on the hydraulic performance of the filter is much greater than that of the flow rate. Compared to mesh filters, disk filters offer better hydraulic performance, with the contaminant capacity of disk filters being approximately three times that of mesh filters. (2) In biogas slurry drip irrigation, the filter combination generally outperforms single filters in terms of hydraulic performance and contaminant removal capacity. Due to the unique nature of the water source in biogas slurry, a selection process for filter combinations was conducted. It was found that when a disk filter is used as the pre-filter and a mesh filter as the post-filter, the overall rate of head loss change is the smallest, and the clogging uniformity is the least. (3) In the entropy weight-TOPSIS comprehensive evaluation, the filter’s operating time and contaminant capacity are key factors affecting its overall performance. From the perspective of improving the operational stability of the biogas slurry drip irrigation system, it is recommended to use a disk filter + mesh filter combination. This study conducts practical measurements on the hydraulic performance, contaminant removal capacity, filtration accuracy, and other indicators of commonly used mesh and disk filters, aiming to provide useful references for the practical application of biogas slurry drip irrigation filters.